1991
DOI: 10.1038/clpt.1991.177
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of quinidine on the disposition of nifedipine, sparteine, and mephenytoin in humans

Abstract: The effects of quinidine on oxidative routes of drug metabolism mediated by different forms of cytochrome P450 were investigated in 10 healthy subjects. Each subject was studied on three different occasions and separately received oral administration of (1) a "cocktail" of nifedipine (5 mg), sparteine sulfate (90 mg), and mephenytoin (100 mg), (2) quinidine sulfate (200 mg), and (3) quinidine sulfate followed by the "cocktail" 1 hour later. Quinidine pretreatment significantly inhibited the aromatization of ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 1 publication
1
15
2
Order By: Relevance
“…Although this observation is based on very few samples and thus not conclusive, it suggests that there may be a relationship between the CYP2D6 genotype and the metabolizm of quinidine. Earlier studies have indicated that although quinidine is a potent inhibitor of CYP2D6 [11–15], it is not a substrate of this enzyme [11, 30–34]. These results are, however, based on data using higher quinidine doses and concentrations than those used in the present study.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Although this observation is based on very few samples and thus not conclusive, it suggests that there may be a relationship between the CYP2D6 genotype and the metabolizm of quinidine. Earlier studies have indicated that although quinidine is a potent inhibitor of CYP2D6 [11–15], it is not a substrate of this enzyme [11, 30–34]. These results are, however, based on data using higher quinidine doses and concentrations than those used in the present study.…”
Section: Discussioncontrasting
confidence: 64%
“…CYP2D6 is a high‐affinity, low capacity enzyme and is saturated at relatively low substrate concentrations. Thus, we cannot exclude that at low quinidine doses/concentrations, CYP2D6 may play a significant role in the metabolism of quinidine, whereas at higher quinidine levels CYP3A4 might become the predominant enzyme [11, 32]. Further studies are required to establish if CYP2D6 is involved in the metabolizm of quinidine at low doses and concentrations of the drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cocktail design offers several advantages through the required knowledge of drug metabolic pathways obtained in a single experimental session involving possible pharmacologic or pathophysiologic effects on enzyme induction or inhibition. Effects such as concomitant drug therapy and liver disease have been evaluated with the use of several different cocktails 2 , 3 , 4 , 5 . Another advantage with a cocktail is that environmental factors do not change during the limited time of the experiment 1 .…”
mentioning
confidence: 99%
“…Clinically relevant DDIs have been observed between quinidine and nifedipine. In two studies, nifedipine exposure (AUC 0-8h ) increased 37% and the formation of the major metabolite decreased about 40% after administration of quinidine, which was attributed to inhibition of CYP3A4-mediated metabolism [16,17]. Therefore, it is important to have a clearer understanding of an interaction between a drug and CYP3A4 if the drug behaves similar to nifedipine.…”
Section: Introductionmentioning
confidence: 95%